Hambatan dan Upaya UMKM Kreatif Menjalankan Usaha Berbasis Syariah di Kota Pekanbaru - Qomariah Lahamid (Lembaga penelitian dan pengabdian kepada Masyarakat, 2018)
This research attempts to find out the barriers and efforts of SMEs sharia-based creative on Pekanbaru, where there are differences with other general SMEs. This study is descriptive and unit of analysis is sharia-based creative SMEs in the city of Pekanbaru. Type of data in the research is primary data. The data collect with interviews and surveys to 40 respondents. Sampling technique in this study is purposive sampling with the criteria that the SMEs label themselves as Sharia-based and creative businesses. The results showed that sharia-based creative SMEs in Pekanbaru City apply some sharia concepts. Some aspects that are observed are products, transactions, human resources and Islamic finance. The barrier of SMEs to apply full sharia based are financing Islamic banking, human resources, and relations with the government. Some activities are training, seminars, and other activities to support more sharia business. Recommendations for the owner of sharia-based creative SMEs to improve the knowledge of sharia business and make business networks as possible and keep in the sharia norms.